Acute and Sub-chronic Oral Toxicity Study of Ammonium Persulfate in Spraque-Dawley Rats - Kim, Yong Soon (Toxicol Res, 2009)
The toxicity test of ammonium persulfate was conducted to ensure of its potential toxic effects according to the single-dose acute oral toxicity study (OECD Guideline 423) and 90-day repeated dose sub-chronic oral toxicity study guideline (OECD Guideline 408) for establishing national chemical management system, and matching in the Globally Harmonized Classification System (GHS) category. In acute oral toxicity study, pasty stool, perineal contamination and temporary body weight decrease were observed after dosing 1st and 2nd challenge (300 mg/kg body weight). All test animals were dead within 6 hours after dosing at 3rd challenge (2000 mg/kg body weight). Therefore, the GHS class of test substance is considered class 4. In sub-chronic toxicity study, body weight changes, food consumptions, hematological, biochemical and pathological examination did not show any noticeable and significant differences between the administered (5, 20, 80 mg/kg body weight) and control (vehicle only) group animals. Based on these results, the no observed adverse effect level (NOAEL) is considered above 80 mg/kg body weight.